Rethinking design and interiors human beings in the built environment - Caan, Shashi (Laurence King Publishing, 2011)
"Rethinking Design and Interiors explores the position of design in relation to our complex and ever-changing world and promotes a deeper knowledge - with input from the arts sciences, and technology - that will support design's integral role in the advancement of humankind in the twenty-first century."--From back cover.